Earthworms (Annelida: Oligochaeta) of the Con Dao archipelago - Tung, Nguyen Thanh; Ngoc, Nguyen Thi Bao; Anh, Nguyen Duc (Academia Journal of Biology, 2021)
The earthworms of the Con Dao archipelago are investigated based on literature and newly collected specimens. A total of 16 species belonging to seven genera in three families are documented in Con Son and Bay Canh islands. The species, Polypheretima grandisetosa (Thai, 1996) is re-described from holotype and freshly collected specimens. All species are imaged for recognition. An identification key to all earthworm species is provided for the Con Dao archipelago.